Cross-Streams Through the Ventral Posteromedial Thalamic Nucleus to Convey Vibrissal Information - Zhang, Huimin; Wang, Xiaojun; Guo, Wenyan; Li, Anan; Chen, Ruixi; Huang, Fei; Liu, Xiaoxiang; Chen, Yijun; Li, Ning; Liu, Xiuli; Xu, Tonghui; Xue, Zheng; et al. (Frontiers in Neuroanatomy, 2021)
Whisker detection is crucial to adapt to the environment for some animals, but how the nervous system processes and integrates whisker information is still an open question. It is well-known that two main parallel pathways through Ventral posteromedial thalamic nucleus (VPM) ascend to the barrel cortex, and classical theory suggests that the cross-talk from trigeminal nucleus interpolaris (Sp5i) to principal nucleus (Pr5) between the main parallel pathways contributes to the multi-whisker integration in barrel columns. Moreover, some studies suggest there are other cross-streams between the parallel pathways. To confirm their existence, in this study we used a dual-viral labeling strategy and high-resolution, large-volume light imaging to get the complete morphology of individual VPM neurons and trace their projections. We found some new thalamocortical projections from the ventral lateral part of VPM (VPMvl) to barrel columns. In addition, the retrograde-viral labeling and imaging results showed there were the large trigeminothalamic projections from Sp5i to the dorsomedial section of VPM (VPMdm). Our results reveal new cross-streams between the parallel pathways through VPM, which may involve the execution of multi-whisker integration in barrel columns.